PK/PD Study of Mycophenolate Mofetil in Children With Systemic Lupus Erythematosus to Inform Model-Based Precision Dosing - Chen, Yewei; Sun, Li; Xu, Hong; Dong, Min; Mizuno, Tomoyuki; Vinks, Alexander A.; Brunner, Hermine I.; Li, Yifan; Li, Zhiping (Frontiers in Pharmacology, 2020)
Objectives To evaluate the mycophenolic acid (MPA, the active form of mycophenolate mofetil (MMF)) PK parameters in relation to clinical response to identify target exposure ranges in pediatric patients with systemic lupus erythematosus (SLE). Methods This was a retrospective study using PK data collected in 67 pediatric patients aged 4 to 18 years with SLE. Target MPA exposures for effective inhibition of SLE activity (as measured by SLE Disease Activity Index (SLEDAI), active SLE was defined as a SLEDAI score of ≥6, and a controlled disease was defined as a SLEDAI score of ≤4) were assessed by receiver operating characteristic (ROC) curve and logistic regression. Exposure-response models were developed to quantitatively describe the relationship between SLEDAI score and AUC0-12 or Ctrough, respectively. Results The MPA AUC0-12 in patients with active SLE was significantly lower than that in patients with inactive SLE. ROC analysis revealed that an AUC0-12 threshold of 39 μg•h/ml or a Ctrough of 1.01μg/ml was associated with the lowest risk of active SLE. Logistic regression analysis revealed that an AUC0-12 of less than 34 µg•h/ml or a Ctrough of less than 1.2 μg/ml probably is associated with active SLE. The results of the exposure-response modeling also indicated that an AUC0-12 less than 32 μg•h/ml or a Ctrough less than 1.1 μg/ml was associated with suboptimal clinical outcome. An AUC0-12 above 50 μg•h/ml or a Ctrough above 1.7 ug/ml was associated with disease control. Conclusions Both AUC0-12 and Ctrough of MPA are predictive of the likelihood of active SLE in pediatric patients receiving MMF. An individualized dosing regimen of MMF, with a target AUC0-12 or Ctrough, should be considered for SLE patients.